Sentimen pengguna aplikasi X terhadap pengembangan ruang baca neo historia: studi netnografi pada fitur reply akun @neohistoria_id - Fina Nurul Zakiyyah (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2026)
This study aims to analyze user sentiment on the X (Twitter) regarding the development of Neo Historia’s reading space as a community-based literacy initiative. This research employed a descriptive qualitative method with a netnographic approach by examining 329 replies from the @neohistooria_id using the keywords “ruang baca” (reading space) and “perpustakaan” (library) during the period between July 2024 – November 2024. The data were analyzed qualitatively through three categories of sentiment (positive, negative, neutral). The findings indicate that positive sentiments include appreciation, support for improving facilities, and user expectations regarding the expansion of the book collection. Negative sentiments are dominated by destructive criticism, skepticism toward management transparency, and negative evaluations of the physical condition of the reading space. Meanwhile, neutral sentiments consist of informational questions, technical comments without emotional expression, and conversations unrelated to the topic discussed. These findings suggest that social media, particularly X, contributes theoretically to the study of public perception in digital spaces and plays a significant role in optimizing communication strategies and the development of reading facilities as part of literacy initiatives.